Estudio de la producción, beneficiado y comercialización de cacao para el sector de Shumiral - Ramírez Guaycha, Byron Patricio (2006)
The present work is part of those "definitive Studies of the Subproyecto Intercantonal of benefitted production and commercialization of cocoa in the low areas of Pucará, Ponce Enríquez and Pijilí", proposal that you development in Agreement with the M. I. Municipality of Ponce Enríquez, The University of Machala through the Department of Linking with the Community of the Ability of Agricultural Sciences and the Foundation Progress and Development PRODE, the project is financed by the PROLOCAL through funds of the Interamerican Bank of Development IDB, the Municipality and the cacaoteros of the intervention area. The surveys were carried out in the properties cacaoteras of the communities of Shumiral to the Canton Camilo Ponce Enríquez of the County of the Azuay, the outlined objectives were: OBJECTIVES: For the Component of: Study of the productive offer and commercialization cacaotera: 1. Integral diagnosis of the productive and commercial offer. 2. Improvement of productive and commercialization systems. For the Component of: "Partner - Organizational - Self-management": 1. integral diagnosis of the structure organizational beneficiary. 2. to outline a structure partner - organizational for viabilizar the installation of the project, with the support of a system of active, equal participation and empoderada with all and each one of the potential partners of the sub-project. As a result of the integral diagnosis of the productive and commercial offer he/she comes off that the drop productivity of the Sector of Shumiral 7.44 qq/ha (fresh + dry) against 8.2 qq/promedio/país and 10 qq average in the area of Orange grove, the goal to the two years of intervention of the project a production of 10.0 qq will be gotten / ha/año in the Sector Shumiral, average that will be competitive for the producing cacaoteros. To achieve 35 increase% in the production it will be necessary a training process, technical attendance and permanent accompaniment to the cacaoteros. In a same way there are 27% of weaknesses the partner - organizational, for which it has been planned the invigoration of the farmer's capacities and the necessity of forming an organizational structure of second grade, with artificial life approved by the organizations involved in the project The intervention proposal is planned for two years of an intensive training process and technical attendance, it will allow to improve the production levels, to implement the proposal of direct commercialization, the middlemen that absorb a great margin of utility without carrying out any investment type, eliminating for it will be implemented it a storing center located in Shumiral and administered by the same organization.